KEANEKARAGAMAN DAN KARAKTERISASI AWAL BAKTERI RHIZOBIUM PADA TANAH RHIZOSFER KEDELAI, KACANG HIJAU, KACANG PANJANG, DAN KACANG TANAH - Af’idzatuttama, Af’idzatuttama; Anwar, Khairul; Amara, Khansa (Institute of Computer Science (IOCS), 2026)
Legume plants play an important role in agricultural systems. Nitrogen is an essential nutrient required by plants for both vegetative and generative growth. Nitrogen-fixing bacteria commonly used in agriculture belong to the genus Rhizobium spp. Rhizobium is a Gram-negative bacterium that inhabits the rhizosphere region of plants. Agronomically, this bacterium has the ability to form symbiotic relationships with leguminous plants, which play a significant role in maintaining soil fertility. Peanut, soybean, yardlong bean, and mung bean were the legume crops used in this study. Isolation of Rhizobium bacteria was carried out using the serial dilution method from 10?¹ to 10??. The isolates obtained were subjected to hemolysis testing and morphological characterization on YEMA (Yeast Extract Mannitol Agar) medium. Blood agar medium was used for the hemolysis test. The highest population of Rhizobium bacteria was found in mung bean and yardlong bean rhizosphere soils, each with 3.0 × 10? CFU/g. Most Rhizobium isolates exhibited milky white, translucent white, and pink colony colors. A total of 16 isolates were obtained from soybean, 16 from yardlong bean, 7 from peanut, and 8 from mung bean. Morphologically, Rhizobium colonies were generally circular, flat, and exhibited whitish-pink to translucent coloration.